Primary surplus and debt projections based on estimated fiscal reaction functions for euro area countries - Martin Plödt; Claire Reicher (Kiel Institute for the World Economy (IfW), 2014)
We project the path of the public debt and primary surpluses for a number of countries in the euro area under a fiscal rule based on a set of estimated fiscal policy reaction functions. Our fiscal rule represents a fiscal analogue to a well-known monetary policy rule, and it is calibrated using country-specific as well as euro area-wide parameter estimates. We then forecast the dynamics of the fiscal aggregates under different convergence, growth, and interest rate scenarios and investigate the implications of these scenarios in projecting the future path of fiscal aggregates. We argue that our forecasting methodology may be used to deliver insights into the medium-run effects of different fiscal policy rules and to provide some early warning of future fiscal pressures.
Keywords: H62; H63; H68; 330; fiscal rules; fiscal policy; euro area; forecasting